Playing to win raising children in a competitive culture - Friedman, Hilary Levey, 1980- (University of California Press, 2013)
"Many parents work more hours outside of the home and their lives are crowded with more obligations than ever before; many children spend their evenings and weekends trying out for all-star teams, traveling to regional and national tournaments, and eating dinner in the car while being shuttled between activities. In this vivid ethnography, based on almost 200 interviews with parents, children, coaches and teachers, Hilary Levey probes the increase in children's participation in activities outside of the home, structured and monitored by their parents, when family time is so scarce. As the parental "second shift" continues to grow, alongside it a second shift for children has emerged--especially among the middle- and upper-middle classes--which is suffused with competition rather than mere participation. What motivates these particular parents to get their children involved in competitive activities? Parents' primary concern is their children's access to high quality educational credentials--the biggest bottleneck standing in the way of, or facilitating entry into, membership in the upper-middle class. Competitive activities, like sports and the arts, are seen as the essential proving ground that will clear their children's paths to the Ivy League or other similar institutions by helping them to develop a competitive habitus. This belief, motivated both by reality and by perception, and shaped by gender and class, affects how parents envision their children's futures; it also shapes the structure of children's daily lives, what the children themselves think about their lives, and the competitive landscapes of the activities themselves"--